ABCG2: recent discovery of potent and highly selective inhibitors. (June 2013) - Lecerf-Schmidt, Florine; Peres, Basile; Valdameri, Glaucio; Gauthier, Charlotte; Winter, Evelyn; Payen, Léa; Di Pietro, Attilio; Boumendjel, Ahcène
ABCG2 impacts oral availability, tissue distribution and excretion of its substrates, including anticancer and anti-infectious drugs. Highly expressed at physiological barriers, its secretion level significantly controls drug distribution. Furthermore, its increased content into many types of cancer may lead to cell chemoresistance. Owing to the clinical relevance of ABCG2 in the multidrug resistance phenomenon, ABCG2 constitutes an appealing therapeutic target to increase drug distribution. Development of ABCG2 inhibitors can be used in combination with anticancer drugs to block the drug secretion from cancer cells. Very recently, an alternative use of ABCG2 inhibitors in enhancing the bioavailability of ABCG2 substrates has emerged. Hence, it is important to investigate ABCG2 inhibitors with high selectivity, high potency and safety. New inhibitors discovered during the last 5 years will be presented and discussed.